1984
DOI: 10.1002/jmv.1890140212
|View full text |Cite
|
Sign up to set email alerts
|

Serological diagnosis of parainfluenza virus infections by enzyme immunoassay with special emphasis on purity of viral antigens

Abstract: Enzyme immunoassay (EIA) for parainfluenza virus type 1, 2, and 3 antibodies was compared with the complement fixation test (CF) as a diagnostic method in 180 patients with respiratory symptoms. The CF test detected rises in parainfluenza virus antibodies in 30 cases, whereas EIA detected 47 rises. Patients with antibody rises in parainfluenza or mumps virus antibodies were studied for cross-reactions by CF, hemagglutination inhibition (HAI), and EIA using purified viral envelope glycoprotein and nucleocapsid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 19 publications
5
29
0
1
Order By: Relevance
“…These results were similar to those of Julkunen (1984) who found that hyperimmune sera against the envelope glycoproteins of mumps virus and parainfluenza type 3 virus did not cross-react with the heterologous virus. In the present study, nine monoclonal antibodies directed against Sendai virus reacted either with mumps virus or parainfluenza type 3 virus, but no monoclonal antibody against Sendai virus reacted with both heterologous viruses simultaneously.…”
Section: Reactivity Of Eight Monoclonal Antibodies Directed Against Dsupporting
confidence: 90%
See 4 more Smart Citations
“…These results were similar to those of Julkunen (1984) who found that hyperimmune sera against the envelope glycoproteins of mumps virus and parainfluenza type 3 virus did not cross-react with the heterologous virus. In the present study, nine monoclonal antibodies directed against Sendai virus reacted either with mumps virus or parainfluenza type 3 virus, but no monoclonal antibody against Sendai virus reacted with both heterologous viruses simultaneously.…”
Section: Reactivity Of Eight Monoclonal Antibodies Directed Against Dsupporting
confidence: 90%
“…antibodies can be employed in a particular study. Intertypic antigenic relationships between paramyxoviruses have been studied previously both with monoclonal (Goswami & Russell, 1983;Ray & Compans, 1986) and polyclonal sera (Goswami & Russell, 1982;Julkunen, 1984). In the present study, three mumps virus monoclonal antibodies directed against different structural proteins reacted with Sendai virus.…”
Section: Reactivity Of Parainfluenza Type 3 Virus Monoclonal Antibodimentioning
confidence: 70%
See 3 more Smart Citations